May Measurement Month 2019: An analysis of blood pressure screening results from Argentina - Salazar, Martin Rogelio Enrique (2021)
The Argentinean Society of Hypertension, in agreement with the May Measurement Month (MMM) initiative of the International Society of Hypertension, implemented for the third consecutive year a hypertension screening campaign. A volunteer cross-sectional survey was carried out in public spaces and health centres during the month of May 2019 across 33 cities in Argentina. Hypertension was defined as systolic blood pressure (BP) ≥140 mmHg and/or diastolic BP ≥90 mmHg based on the mean of the second and third BP measurements, or in those on treatment for high BP. A total of 94 523 individuals (53.9 ± 17.8 years old, 55 231women and 39 292 men), were evaluated. The age and sex standardized mean BP was 124.7/77.2 mmHg. Among participants, 34.7% were overweight (25-29.9 m/kg2) and 28.7% had obesity (≥30 m/kg2). Individuals identified as being overweight had BP 3/2 mmHg higher and individuals with obesity 6/4 mmHg higher than those with normal weight. The prevalence of hypertension was 52.5%. Although 81.1% were aware and 77.7% were on antihypertensive treatment, only 46.0% of all individuals with hypertension had their BP controlled. Moreover, 19.8% of those not on any antihypertensive medication were found with raised BP. The low level of control of hypertension generates the critical need for the development of community-based prevention strategies reinforcing strategies to increase the awareness and control of hypertension.